Sosialisasi Dampak Positif dan Negatif Penggunaan Gadget dalam Perkembangan Teknologi Digital Bagi Remaja - Fathia Azzahra Sofianti; Ade Leni Nuraeni; Prihartini Dwi Wulandari (CV. ITTC INDONESIA, 2025)
The use of gadgets in today's digital technology has become a common phenomenon, especially among teenagers. Gadgets such as smartphones, tablets, and laptops can make it easier for teenagers to communicate, access a wide range of information, enhance creativity, and facilitate online learning. However, excessive use of gadgets can certainly have negative effects such as addiction, cyberbullying, decreased physical health, and academic performance. The purpose of this Community Service (PKM) activity was to provide an understanding of the positive and negative impacts of gadget use and to encourage students at SMAN 6 Tangerang Selatan to use gadgets wisely in the development of digital technology. The methods used included lectures and question and answer sessions. The results of the socialization show that students at SMAN 6 South Tangerang have increased their understanding of the positive and negative impacts of gadget use. This PKM activity has also been able to encourage a change in students' attitudes towards gadget use, as seen from their self-reflections that they will use gadgets wisely